Litomosoides silvai (Nematoda: Onchocercidae) parasitizing Akodon montensis (Rodentia: Cricetidae) in the southern region of Brazil - Trevisan Gressler, Lucas (2017)
In the present study, Litomosoides silvai parasitizing Akodon montensis in the southern region of Brazil is reported for the "rst time. New morphological information is provided for some structures of this nematode species, such as a #attened cephalic extremity, presence of two dorsal cephalic papillae, female tail with a constriction at its tip, “s” shaped vagina, spicules characteristic of the carinii species group and micro"laria tail constricted at the tip. $is nematode was found parasitizing the thoracic cavity with a prevalence of 10% (2/20), mean intensity of 4 (6/2), mean abundance of 0.4%(8/20) and range of infection of 2-6 specimens per host, in southern Brazil. $is occurrence of L. silvai in A. montensis is a new geographical record for southern Brazil, in the Upper Paraná Atlantic Forest ecoregion of the northwestern region of Rio Grande do Sul, which is part of the Atlantic Forest biome.